A Psychometric Evaluation of the Stanford Expectations of Treatment Scale (SETS) in the Context of a Smoking Cessation Trial. Issue 12 (30th July 2022) - Ferkin, Adam C; Tonkin, Sarah S; Maguin, Eugene; Mahoney, Martin C; Colder, Craig R; Tiffany, Stephen T; Hawk, Larry W
Abstract: Introduction: Although treatment outcome expectancies (TOEs) may influence clinical outcomes, TOEs are rarely reported in the smoking cessation literature, in part because of the lack of validated measures. Therefore, we conducted a psychometric evaluation of TOEs scores with the Stanford Expectations of Treatment Scale (SETS) in the context of a smoking cessation clinical trial. Methods: Participants were 320 adults enrolled in a randomized controlled trial of extended versus standard pre-quit varenicline treatment for smoking cessation (clinicaltrials.gov ID: NCT03262662). Across an 8-week treatment period, we examined the nature and stability of the factor structure using confirmatory factor analysis (CFA), evaluated discriminant validity by examining correlations with abstinence self-efficacy and positive/negative affect (PA/NA), and assessed internal consistency and test–retest reliability of SETS scores. Results: CFAs supported a 2-factor structure that was stable (ie, invariant) across weeks. Positive and negative TOEs were each reflected in three-item subscales that exhibited acceptable to excellent internal consistency (Cronbach's alphas ≥ .77). Positive and negative TOEs were modestly correlated with PA and NA (all | r s| <.27, p < .05). Positive TOEs, but not negative TOEs, were moderately correlated with abstinence self-efficacy ( r s = .45 to .61, p < .01). Both positive and negative TOEs scores demonstrated moderate test-retest reliability between assessments ( r s = .54 to .72). Conclusions: SETS scores generally reflect a valid and reliable assessment of positive and negative TOEs in a sample of adults enrolled in a smoking cessation trial. The SETS appears to be a reasonable option for assessing TOEs in future smoking treatment studies. Implications: Assessments of treatment outcome expectancies are rarely reported in the smoking cessation literature. The present results support the validity and reliability of the SETS scores among adults seeking treatment for their smoking behavior.